Impacts of aquaculture on the management of estuaries in India - RAMACHANDRA BHATTA AND MAHADEV BHAT (Environmental Conservation 25 (2): 109-121, 1998)
The emergence of commercial aquaculture in estuaries along the coast of Karnataka, India, has resulted in the breakdown of traditional methods of resource management and adverse impacts on the coastal environment. Based on field survey, personal discussions and published literature, we analyzed the evolution of different market (economic), traditional, and regulatory institutions governing the use of estuarine resources in the study area over the last three decades, and identified the environmental and social impacts of this evolution. In the past, informal associations of farmers in the estuarine floodplains had managed lands for raising crops and brackish-water fish in a sustainable way. In recent years, under economic and political pressures, landowners leased their lands to commercial shrimp-producers. A rapid growth in the production of commercial shrimp, employment of unsustainable production technologies, and laxity in environmental regulation have caused negative ecological and economic impacts on communities dependent on estuarine resources. Through a recent order from the Indian Supreme Court, environmentalists and the affected communities have sought to ban commercial aquaculture in ecologically-sensitive areas. While this court order awaits implementation, several policy options are here suggested for local, state and central governments in India in order to protect the estuarine environment.